Compressive mechanics of warp-knitted spacer fabrics. (October 2021) - Guo, Haiyang; Liu, Yanping; Xia, Yumin; Hu, Hong; Wang, Yiming; Qiu, Gao
This paper aims to identify the underlying physical mechanism for the compression deformation of a warp-knitted spacer fabric with a typical structure with experimental and theoretical studies. Compression tests were carried out to measure the load–displacement relationship of the fabric. The structural features of the spacer yarns were photographed by a microscope at different displacements during the compression test. A theoretical model based on elastica theory was developed to describe the compression behavior of the fabric by introducing the effect of complex geometry of the spacer yarns. A comparison between the experimental results and theoretical calculations was also conducted. Four distinctive stages including initial stage, elasticity stage, plateau stage and densification stage were identified and their underlying physical mechanisms were explained based on experimental observations and theoretical calculations. The model could provide an in-depth understanding on the deformations of spacer yarns of spacer fabrics under compression.